Valeur, fonction et médiation dans les espaces naturels sensibles : une patrimonialisation inachevée de la nature. Exemples dans les Pays de la Loire - Celine Barthon; Céline Chadenas; Arnaud de Lajartre; Antoine Pancher (VertigO)
The following article proposes an assessment of the use of the « Espaces Naturels Sensibles » (Sensitive Natural Areas) or ENS programme within the five “départements” (counties) of the region “Pays de la Loire”. We started from the observation of an unequal and diversified use of the programme among counties. That disparity reveals large differences in the appropriation of ENS concerning the aims (whether legal or administrative) as well as the stakeholders/users. We were able to put forwards a common feature in the evolution of the criteria for the selection of ENS sites : the growing importance of ecological criteria. This tendency illustrates the drift from identifying emblematic sites – natural, scenic, cultural or historical sites – as heritage to identifying biodiversity in an area as heritage. The two tests sites’ analysis (Maine-et-Loire and Loire-Atlantique), and in particular of their mediation mechanisms, will be the opportunity of illustrating this new tendency, but more importantly, of highlighting a relevant change in values for the use of these areas. We will then be able to refine our understanding of how the identification of nature as heritage works.